PATRONASE DAN MODULAR PADA CALONLEGISLATIF PEREMPUAN NEWCOMER - Sasmita, I Made Adhi Purwa; Noak, Piers Andreas; Erviantono, Tedi (Jurnal Nawala Politika, 2025)
This research aims to  determine  how  patronage  clientelism  and  political  modularity are in  the  2019  legislative  elections  in  Abiansemal District. This  study  is framed using the theory of  patronage clientelism  and  theory  of  modular  parties as an analytical tool  for  the  problems  in  this  research.  The  research  method  used in this research is  qualitative  descriptive  research  with  primary  and  secondary data usage, because it describes and illustrates phenomena that  exist, both natural and human engineering, which pay more  attention  to  the  characteristics, quality, interrelationships between activities in relation to patronage relationships. and modular in legislative  elections.The  results  of  this  study  are:  first, the relationship between  actors  and  voters  (patron-client)  tends  to  function  as a use for candidate identification and  vote-seeking  based  on  kinship  relationships and reciprocal relationships between actors  and  voters.  Second,  Ni Luh Sekarini used the  role  of  brokers  and  parties  (modular  parties)  in  the  process of winning through mass mobilization. Third,. theory of modular parties dominates in terms of proving and utilizing research findings Keywords : Ni Luh Sekarini, Patronage-Clientelism, Modular parties